Արցախյան հարցի կարգավորման ուղղությամբ Ամերիկայի Հայ Դատի հանձնախմբի գործունեության արձագանքները Բեյրութի «Ազդակ» օրաթերթում - Շարոյան, Էլեն (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
There are several dozen structures of the Armenian National Committee in the Armenian Diaspora, among which the Armenian National Committee of America stands out for its activity and influence. One of the main activities of the latter is to promote the settlement of the Nagorno-Karabakh conflict. The settlement of the Karabakh problem and the international recognition of the Republic of Artsakh have always been the focus of attention of the Armenian newspaper Azdak. The newspaper professes national ideology and wages a selfless struggle from the standpoint of Armenian nationality and Armenian demands. The contemporary newspaper publications mainly concern the Republic of Armenia, Artsakh, the Diaspora, the Armenian community of Lebanon and the activities of the ARF. Every year, Azdak also publishes its annual review issue, which covers the most important events that took place during the year, international transition, and also publishes analytical articles. Azdak actively covers the activities of the Armenian National Committee, which is not limited to providing information, but regularly expresses its opinion and attitude towards the committee’s initiatives. The newspaper covers the activities of the committee in extensive and diverse publications, emphasizing it as a structure expressing the common interests of the Armenian people, seeking a fair solution to the Karabakh problem within the framework of the principle of self-determination of nations.
Keywords: Պարբերականներ